Affordability Assessment to Implement Light Rail Transit (LRT) for Greater Yogyakarta - Anjang Nugroho; Imam Muthohar (Journal of the Civil Engineering Forum, 2013)
The high population density and the increasing visitors in Yogyakarta aggravate the traffic congestion problem. BRT (Bus Rapid Transit) services, Trans Jogja has not managed to solve this problem yet. Introducing Light Rail Transit (LRT) has been considered as one of the solutions to restrain the congestion in Greater Yogyakarta. As the first indication that the LRT can be built in Greater Yogyakarta, the transportation affordability index was used to understand whether the LRT tariff was affordable. That tariff was calculated based on government policy in determining railway tariff. The forecasted potential passengers and LRT route have been analyzed as the previous steps to get LRT tariff. Potential passenger was forecasted from gravity mode, and the proposed LRT route was chosen using Multi Criteria Decision Analysis (MCDA). The existing transportation affordability index was calculated for comparison analysis using the percentage of the expenditures for transportation made by monthly income of each household. The result showed that the LRT for Greater Yogyakarta was the most affordable transport mode compared to the Trans Jogja Bus and motorcycle. The affordability index of Tram Jogja for people having average income was 10.66% while another people with bottom quartile income was 13.56%.Keywords: Greater Yogyakarta, LRT, affordability.